Delayed adolescent growth in homozygous sickle cell disease. Issue 5 (November 1994) - Singhal, A; Thomas, P; Cook, R; Wierenga, K; Serjeant, G
Abstract : Analysis of the growth abnormalities in sickle cell disease has been limited by the lack of longitudinal observations in individuals, and by an inability to quantitate the observed patterns. To investigate the timing and pattern of the adolescent growth spurt, longitudinal observations of height from the Jamaican cohort study were fitted to a mathematical model of growth (Preece-Baines model 1). The study included 44 children with homozygous sickle cell (SS) disease, 44 age and sex matched subjects with sickle cell haemoglobin C (SC) disease, and 44 age and sex matched controls with normal (AA) haemoglobin. Compared with AA controls, the onset of the adolescent growth spurt was delayed in SS disease by 1.4 years (95% confidence interval 0.8 to 2.0) with no significant sex difference. The age at peak height velocity was delayed by 1.6 years (0.9 to 2.3) in SS compared with AA subjects but the adolescent growth of SS children was otherwise normal and there was no difference in the attained height by age 17.9 years. The growth spurt was not delayed in SC disease. The age at menarche in girls with SS disease (mean (SD) 15.4 (1.3) years) was significantly later than girls with SC disease (13.7 (1.7) years) and those with AA haemoglobin (13.1 (1.3) years) but these genotype differences were no longer significant after controlling for the delay in the adolescent growth spurt. The normally coordinated but slightly delayed pattern of growth and normal adult heights suggests a good prognosis for adolescent growth delay in SS disease. Most children with SS disease can therefore be reassured on the outcome of retarded adolescent growth.